Atherosclerosis in a cockatiel (Nymphicus hollandicus): Case report in Costa Rica - Valverde Rodríguez, Beatriz (2022)
A ten-year old female cockatiel (Nymphicus hollandicus) that suddenly died during the veterinary examination was analyzed through histopathology in the laboratory of the Avian Pathology Diagnostic Unit, School of Veterinary Medicine, Universidad Nacional. Macroscopic lesions showed thickening of the ascending aorta and of the aortic bifurcation, multiple nodules and tortuous vessels. Atherosclerotic lesions with variable severity were also observed. The present case report provides a description and characterization of the histopathological lesions of arteriosclerosis. The available diagnostic methods, preventive measures, and possible treatments against this avian pathology in Costa Rica are mentioned.